Сто великих географических открытий - Баландин Рудольф Константинович (100 великих, 2008)
Экземпляры: (20170721) / Инвентарный номер: 33759 / Цена: 105.10 / Сис.шифр: 26.8г / Авт.знак: Б 20 / ББК: 26.8г